ARCHAEOLOGICAL SURVEYS IN SULEIMAN-STALSKY DISTRICT OF DAGESTAN IN 2015 - Abiev, A K (History, Archeology and Ethnography of the Caucasus, 2016)
The article presents the results of archaeological investigations carried out in Suleiman-Stalsky district of the Dagestan Republic. During the excavations in the area Pirenyatag the researchers revealed a burial mound dating to the 4th-5th centuries AD.